The Colonisation of South Africa: A unique case - Erna Oliver; Willem H. Oliver (HTS Teologiese Studies/Theological Studies, 2017)
From the 15th century onwards, most of the countries in Africa have been colonised by theEuropean world powers, Great Britain, France, Portugal, Germany, Spain, Italy and Belgium.South Africa was officially colonised in 1652. Apart from the European colonisation beingexecuted from the south of the continent, South Africa also experienced a migration andinvasion of people groups from the north. The indigenous people groups, inhabiting thecountry long before these two groups arrived there, will be discussed as background to the restof the article. A few factors that made the colonisation of South Africa unique within theAfrican context will be discussed.